Taxifolin as a Major Bioactive Compound in the Vasorelaxant Effect of Different Pigmented Rice Bran Extracts - Seong, Eun-Hee; Gong, Dal-Seong; Shiwakoti, Saugat; Adhikari, Deepak; Kim, Hyun Jung; Oak, Min-Ho (Frontiers in Pharmacology, 2022)
Cardiovascular disease is one of the leading causes of morbidity and mortality in recent years. The intake of polyphenol rich diets has been associated with improved cardiovascular function and reduced cardiovascular risks. Oryza sativa L. is one of the most common cereals worldwide. Rice bran, a byproduct of the rice milling process, contains many bioactive ingredients, including polyphenols, polysaccharides, proteins, and micronutrients. It is also consumed as a healthy diet in the form of rice bran oil and powder in many Asian countries like Japan, South Korea, and India for its several health benefits as a natural antioxidant. Thus, this study evaluated the vasorelaxant effect of ethanolic extracts of brown, green, red, and black rice bran and investigated its underlying vasorelaxant mechanism. Among the four rice bran extracts (RBEs) examined, the red rice bran extract (RRBE) had a strong endothelium-dependent vasorelaxant effect, which was markedly prevented by N-ω-nitro-L-arginine [endothelial nitric oxide synthase (eNOS) inhibitor], wortmannin [phosphoinositide-3 kinase (PI3K) inhibitor], and 1H-[1,2,4]oxadiazole[4,3-alpha]quinoxalin-1-one (inhibitor of guanylate cyclase). Likewise, RRBE induced the phosphorylation of eNOS and Src in cultured endothelial cells, thereby stimulating NO formation. Altogether, these findings propose that RRBE induces endothelium-dependent relaxation, involving at least in part, NO-mediated signaling through the PI3K/eNOS pathway. Further, LC-PDA analysis conducted on the four RBEs also revealed that RRBE highly contained taxifolin, which is an active flavanonol that induces endothelium-dependent vasorelaxation, compared to other RBEs. Subsequently, the underlying mechanism of taxifolin was assessed through vascular reactivity studies with pharmacological inhibitors similar to that of RRBE. These findings deciphered a distinct difference in vasorelaxant effects between RRBE and the other RBEs. We also observed that RRBE induced a potent endothelium-dependent NO-mediated relaxation in coronary artery rings, which involved the Src/PI3K pathway that activates eNOS. Additionally, taxifolin exhibited, at least in part, similar vasoprotective effects of RRBE. Therefore, we propose that RRBE may serve as natural sources of functional phytochemicals that improve cardiovascular diseases associated with disturbed NO production and endothelial dysfunction.